Afghanistan’s raw materials policy regarding rare earth elements after the Taliban victory - Kamprowski, Rafał (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2024)
The Taliban victory in Afghanistan in 2021 has not only raised geopolitical concerns but has also sparked questions about the state’s policies and strategies concerning its rare earth elements reserves. The main objective of the presented article is to indicate how the current political change in Afghanistan may affect the raw material policy regarding the extraction of rare earth elements, taking into account geopolitical factors. Rare earth elements are a group of critical minerals that are of great importance to modern technologies, ranging from electronics and renewable energy to defence systems. Afghanistan is known to possess significant deposits of these valuable resources, which have the potential to play a crucial role in global supply chains, especially in the face of ongoing rivalry between the People’s Republic of China and the United States of America. The research problem of the considerations undertaken in this article is to assess the key challenges and opportunities in harnessing Afghanistan’s rare earth element resources after the Taliban’s return to power. The research conducted shows that despite having a significant amount of rare earth elements, Afghanistan lacks the infrastructure necessary to extract and process these valuable minerals. After the Taliban victory, the newly established government sees the potential benefit in extracting rare earth elements and is willing to align itself with China to exploit them. Zwycięstwo Talibów w Afganistanie w 2021 r. nie tylko wzbudziło obawy geopolityczne, ale także wywołało pytania o politykę i strategie państwa dotyczące rezerw metali ziem rzadkich. Głównym celem niniejszego artykułu jest wskazanie, jak obecne zmiany polityczne w Afganistanie mogą wpłynąć na politykę surowcową w zakresie wydobycia metali ziem rzadkich, uwzględniając czynnik geopolityczny. Omawiane metale to grupa minerałów krytycznych o ogromnym znaczeniu dla nowoczesnych technologii, począwszy od elektroniki i energii odnawialnej, po systemy obronne. Wiadomo, że Afganistan posiada znaczne złoża tych cennych zasobów, które mogą potencjalnie odegrać kluczową rolę w globalnych łańcuchach dostaw, zwłaszcza w obliczu nieustającej rywalizacji między Chińską Republiką Ludową a Stanami Zjednoczonymi. Problem badawczy podjętych w tym artykule rozważań polega na ocenie kluczowych wyzwań i szans w wykorzystaniu metali ziem rzadkich w Afganistanie po powrocie Talibów do władzy pomimo zawiłości geopolitycznej. Z przeprowadzonych badań wynika, że pomimo posiadania znacznych ilości pierwiastków ziem rzadkich, Afganistanowi brakuje infrastruktury niezbędnej do wydobywania i przetwarzania tych cennych minerałów. Po zwycięstwie Talibów, nowo utworzony rząd dostrzega potencjalne korzyści z wydobycia metali ziem rzadkich i jest skłonny sprzymierzyć się z Chinami w celu ich eksploatacji.
Polityka surowcowa Afganistanu dotycząca metali ziem rzadkich po zwycięstwie Talibów
Keywords: rare earth elements; Afghanistan; raw materials policy; Taliban; metale ziem rzadkich; Afganistan; polityka surowcowa; Talibowie